PROJECT BASED LEARNING DALAM MENINGKATKAN KETERAMPILAN PROSES SAINS: KAJIAN LITERATUR - Munawwarah, Munawwarah; Reinard, Marcindy; Fatkhulloh, Shoffan; Syakur, Akhmad (Universitas Cokroaminoto Palopo, 2025)
This study aims to examine the impact of Project-Based Learning (PjBL) on students’ science process skills (SPS) in science education through a systematic literature review. Out of 70 initially identified articles, 30 were shortlisted, and 14 were ultimately selected based on their relevance and methodological rigor. The reviewed studies were obtained from open-access journals and employed various research designs, including quasi-experimental, classroom action research, qualitative case study, and research and development (R&D) approaches. A systematic review protocol was applied, comprising stages of identification, title and abstract screening, and full-text assessment to ensure inclusion quality. Data were analyzed through the extraction of article characteristics, research design, educational level, science domain, SPS instruments, major findings, and pedagogical mechanisms. The findings indicate that most studies reported significant enhancement of SPS following the implementation of PjBL, with the most frequently improved dimensions being observation (64%), classification (36%), experimental planning (50%), hypothesis formulation (36%), and communication (29%). Supporting factors for effective implementation included the integration of local contexts (ethnoscience), the use of interactive digital media (e.g., comics, Lectora applications), validation of learning materials, teacher scaffolding, and student collaboration, whereas studies reporting non-significant effects were mainly constrained by poor adherence to PjBL syntax and limited project duration. Overall, the results affirm that PjBL holds strong potential for enhancing SPS across various areas of science learning, particularly when supported by coherent pedagogical mechanisms, consistent instructional design, sufficient teacher facilitation, and the use of contextualized media to maximize its educational effectiveness.